Desenvolvimento de formulação para bolo contendo farinha de maca e yacon - Tormena, Marcela Marta Lazaretti (2016)
This work describes the development of an optimized chocolate cake formulation with partial substitution of wheat flour by a mixture of yacon flour and maca flour. The chosen tubercles are functional foods with benefits to human health, as antioxidant activity and prebiotic effect. The influence of the proportions of the flours, as the amount of water added to the batter, were evaluated through the results of sensory analysis, colorimetry, texture profiling and specific volume. The simplex-centroid experimental design was proposed for the three mixture variables (flours proportions) and one process variable (amount of water added to the batter) in three distinct levels. The consumers were segmented through the k-means technique, grouped by their overall acceptability of the cakes. A regression model for the overall acceptability was constructed for both groups, with a R2adjusted of 92.5 % for group 1 and 98.9 % for group 2. The sequential simplex method was used to optimize the formulation for group 1 (49 % wheat, 37 % yacon, 14 % maca and 140 mL of water) and, group 2 (35 % wheat, 65 % yacon, 0 % maca and 120 mL of water). It was proposed a third formulation with greater maca content (32 %) and minimal effect on overall acceptability for both groups. In general, the sensory evaluation results indicated that the presence of yacon increases the acceptability of the cakes, even when maca was added, which alone showed less desirable. A significant correlation was observed between the overall acceptability of the cakes and their flavor. In addition, the sensory evaluation of color was found strongly correlated to darker cakes and saturated browns. The free-choice profiling was applied to the three optimized formulations along with two control formulations. The data acquired was evaluated with common components and specific weights analysis. The results, presented as similarity map and subject space, made directly observable the effects of wheat substitution by yacon and maca over the sensory characteristics of the produced cakes. The correlation of the common components with the consumers’ attributes was used for sensory description of samples. Thus, a greater proportion of maca enhances the brown color, but also the burnt aroma and taste of the cakes. Whereas, a higher proportion of yacon produces a better appearance, softness, sweetness and increased chocolate flavor. This corroborates the claim that the replacement of wheat by yacon in the produced cakes brings improvements to their sensory characteristics, while adding maca is clearly deleterious to them.